2019
DOI: 10.1093/scan/nsaa001
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring in emotion regulation: behavioral decisions and neural consequences

Abstract: Monitoring and deciding how to adjust an active regulatory strategy in order to maximize adaptive outcomes is an integral element of emotion regulation, yet existing evidence remains scarce. Filling this gap, the present study examined core factors that determine behavioral regulatory monitoring decisions and the neuro-affective consequences of these decisions. Using a novel paradigm, the initial implementation of central downregulation strategies (distraction, reappraisal) and the emotional intensity (high, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Research has shown that the self-reported ability to discontinue maladaptive strategies and switch to adaptive strategies is associated with fewer depressive symptoms (Kato, 2015, 2017). Although experimental research on this component is relatively sparse, a few recent studies demonstrated that switching from reappraisal to distraction in the face of high-intensity negative images was associated with larger modulation in neural activity associated with emotional processing (Ilan, Shafir, Birk, Bonanno, & Sheppes, 2019) and that the switching frequency predicted better adjustment when it was in accord with internal physiological response (Birk & Bonanno, 2016). These findings provided support for the importance of monitoring the efficacy of an initial strategy and modifying or replacing ineffective strategies when necessary.…”
Section: Context Sensitivity Repertoire and Response To Feedbackmentioning
confidence: 99%
“…Research has shown that the self-reported ability to discontinue maladaptive strategies and switch to adaptive strategies is associated with fewer depressive symptoms (Kato, 2015, 2017). Although experimental research on this component is relatively sparse, a few recent studies demonstrated that switching from reappraisal to distraction in the face of high-intensity negative images was associated with larger modulation in neural activity associated with emotional processing (Ilan, Shafir, Birk, Bonanno, & Sheppes, 2019) and that the switching frequency predicted better adjustment when it was in accord with internal physiological response (Birk & Bonanno, 2016). These findings provided support for the importance of monitoring the efficacy of an initial strategy and modifying or replacing ineffective strategies when necessary.…”
Section: Context Sensitivity Repertoire and Response To Feedbackmentioning
confidence: 99%
“…Mehta et al, 2017;Milyavsky et al, 2019) with evidence that participants are more willing to regulate their emotional responses to high-intensity images compared to low-intensity images (Mehta et al, 2017) and that intensity influences whether people choose to switch or maintain a regulation strategy (e.g. Birk & Bonanno, 2016;Dorman-Ilan et al, 2020;Murphy & Young, 2020). The intensity of the emotion was found to have a very large-sized relationship with both intentions to regulate (r + = 0.46) and the choice of strategy (r + = 0.61) (see Table 2).…”
Section: Affective Determinantsmentioning
confidence: 99%
“…prompt people to consider whether to continue regulating and, if so, how), studies which examine the monitoring stage of emotion regulation (e.g. Dorman-Ilan et al, 2020) can also help us to understand whether and how people choose to regulate their emotions.…”
mentioning
confidence: 99%
“…12 participants were excluded because they had significant completion time delays, defined as 30 min or more than the expected 45 min duration (note that actual average completion duration was 47 min, and that for 11 of these participants, it took 80 min or more to complete the study). Three participants were excluded due to failure to comply with the experimental instructions: when describing how they implemented their chosen strategies (see details below), these participants made more than 50% errors in total and/or more than 50% errors for a specific strategy (i.e., a conservative exclusion criterion in previous emotion regulation studies 33 , 37 ). Last, three participants were excluded because they failed 50% or more of random attention checks (in which they were instructed to press a certain number) that were embedded in a set of questionnaires filled out at the end of the experiment (see details below).…”
Section: Studymentioning
confidence: 99%
“…Participants first learned how to implement distraction and reappraisal (two examples for each strategy, order of learning was randomized across participants 33 , 37 . Distraction instructions involved disengaging attention from the negative content of the sentences by producing unrelated neutral thoughts (e.g., thinking about daily activities, familiar places, or geometric shapes).…”
Section: Studymentioning
confidence: 99%